Application of Technology in the Digital Era Education - Harwati Hashim (International Journal of Research in Counseling and Education, 2018)
The fact that technology plays a much larger role in the digital era than it did for previous generations has made today’s generation having a high level of technological literacy. The increase in this literacy coupled with recent technological advances has led to the expansion of technology in education. From the millennial to Gen-Z, these are the generations that are coming into the classroom today and they share unique characteristics that define their generations.  These generations expect to be engaged in their learning and they do not do well being passive learners.  Hence, technology has to be embraced in today’s education and teachers have to apply technology as part of the students learning.  This paper reviews the generations of learners that teachers are having today and how these generations impacted the transformation of education in the digital era.  This paper also presents some of the emerging technologies and discusses the needs of pedagogical transformation to invent new forms of teaching and learning as well as the importance of redesigning and rethinking education in the digital era.